Implantação de Firewall PfSense - Neves, Filipe Campos das (2014)
This work presents research and applications necessary for implementing a Firewall in an open source software called pfSense in companies that have less revenue to spending in the area of security, but still need the security of your data either internally or even to external environment. This application is necessary due to the great development of the corporate communications market that brought with it malicious people that make use of mechanisms for the theft of information or even services and products. This document contains the result of the implementation of the pfSense Firewall set to meet the demand of companies using security mechanisms to prevent attacks and information theft.